Understanding the Brahma Kumaris - Whaling, Frank (Understanding faith, 2012)
The Brahma Kumaris are a new spiritual tradition. The movement now has over 450,000 adherents world-wide in more than 100 countries. In this book Frank Whaling seeks to understand the Brahma Kumaris. As with all spiritual traditions, the Brahma Kumaris are different, bewildering, fascinating in their newness and in their complexity